Effects of Anesthetics on Barrier Tissue Function. (21st October 2019) - Wang, Fujing; Li, Yanhui; Cui, Changlei; Xue, Zhaoping; Ma, Haichun
Abstract : Anesthetics have long been proven to have additional effects other than anesthesia on different organs and tissues of the human body. Barrier tissues play critical roles in human health and diseases, yet the impacts of anesthetics on barrier tissues are still not clear. This review article is aimed at summarizing different effects of anesthetics on the skin, the respiratory, and intestinal membranes from two aspects: inflammation/immunity and ischemia-reperfusion. Among volatile, intravenous, and local anesthetics, volatile anesthetics are less influential on barrier ischemia-perfusion function. Although direct comparisons between volatile and the other two types of anesthetics are still lacking, volatile anesthetics appear to have stronger anti-inflammatory effects on different barrier tissues through various mechanisms. These results suggested that when treating patients with barrier tissue complications, volatile anesthetics can provide better therapeutic outcomes.